Politikern som politikerföraktare: Thomas Bodströms Rymmaren och den retoriska situationen - Ullén, Magnus (Tidskrift för litteraturvetenskap, 2009)
The Politician as Distruster of Politicians. Thomas Bodström’s The Runaway and the Rhetorical Situation. This article proposes that we view literary texts as a special case of what American rhetorician Lloyd F. Bitzer calls the rhetorical situation. Just as rhetoricians have situated the speech within the rhetorical situation, the literary text may productively be situated within what I call the literary situation. Literature thus conceived could be described as a process in which kairos – the opportunity to exploit the circumstances of the moment – is transferred from the writer to the reader. That such a theoretical point of departure provides us with a better opportunity to investigate the ideological dimension of literature is demonstrated through a reading of Rymmaren (The Runaway), the first novel by former Swedish Minister for Justice, Thomas Bodström. A political thriller largely set in the Governmental Offices, it was dismissed by critics as lacking literary value but sold well nevertheless. The novel is thus a concrete example of how ethos has gained importance at the expense of logos in contemporary literature. Its attraction does not depend upon how well Bodström writes, but upon who he is: as former minister, he can claim to provide an inside view of the scenes from the political environment he depicts. While the novel shows Bodström being adept at using fiction for political purposes, it also exposes an ideological emptiness which suggests that politics in the 21st century has become a matter of simulation rather than representation.